Moringa Seedling Raising: A Tool for Wealth Creation and Youths Empowerment in North Eastern Nigeria - Garba, A. S; Abdulhamid, A.; Bishir, U. S; Dankade, U. (Kashere Journal of Education, 2021)
The success of agricultural practice or training in any country can be considered a key factor in the country’s growth, wealth creation, youth empowerment and technological development. For a country to achieved food sufficiency, its agricultural sector must play a vital role. A country like Nigeria which its population is rapidly growing, youth engagement into Moringa seedling for skill acquisition is very vital. The paper focused on problems of youth unemployment, level of youth unemployment in the north eastern Nigeria, implications of poor socio-economic status, Moringa science-proven benefits, Moringa seed economics and marketing value, agriculture as a source of employment and wealth creation. It was recommended that, Nigerian youth should equip themselves with basic knowledge of Moringa seedling raising for youth employment and wealth generation which can be achieved through research, training, seminars, conferences and workshops organized by the government and other stake holders of the education and agriculture and the higher institutions of learning should provide Moringa entrepreneurship training centers across the country.